Hubungan Seksio Sesarea Crash dengan Luaran Maternal di RSUP Dr.Sardjito - Satriagraha, Oky Ardian; Prawitasari, Shinta; Siswishanto, Rukmono (JURNAL KESEHATAN REPRODUKSI, 2024)
Background: Crash caesarean section is performed because there is a life-threatening condition to the mother or fetus. The duration between a decision is made to perform a caesarean section until delivery the baby is termed decisions to delivery interval (DDI) or response time. Response time of 30 minutes from the decision to baby delivered is considered to prevent complications and worsen maternal conditions.Objective: To assess the relationship between response time in crash caesarean section with maternal outcome at Dr. Sardjito Hospital.Method: This study was cross sectional method using secondary data from the medical record. The subjects were all pregnant women who underwent crash caesarean section and met the inclusion criteria from January 2021 to December 2022 at Dr. Sardjito Hospital.Results and Discussion: There were 38 cases that met the criteria from 114 cases of crash caesarean section during the period January 2021 to December 2022. From the data obtained, response time of £ 30 minutes was 4 (10,5%) cases and response time > 30 minutes was 34 (89,5%) %) cases. There was no significant relationship between the duration of response time and the maternal outcomes of ICU care, blood transfusion, length of hospital stay, or surgical wound infection (p>0,05). From bivariate analysis, maternal outcomes ICU care was statistically significant relationship of preoperative Hb level <8 g/dL (p=0,003; RR 2,500; 95% CI 1,613-3,875) and severe antepartum hemorrhage (p=0,000; RR 9,880; 95% CI 1,484-65,787). From bivariate analysis, severe antepartum hemorrhage was statistically significant against maternal outcomes blood transfusion (p=0,000; RR 2,600; 95% CI 1,307-5,171).Conclusion: There was no relationship between the duration of response time for crash caesarean section based on maternal indications with maternal outcomes (ICU care, blood transfusion, length of hospital stay, and surgical wound infections) at Dr. Sardjito Hospital. There is a significant relationship between severe antepartum hemorrhage with maternal outcomes of ICU care and blood transfusion. Keywords: crash caesarean section, response time, DDI, maternal outcome